The effect of Nb on grain boundary segregation of B in high refractory Ni-based superalloys. (September 2017) - Antonov, Stoichko; Huo, Jiajie; Feng, Qiang; Isheim, Dieter; Seidman, David N.; Helmink, Randolph C.; Sun, Eugene; Tin, Sammy
Abstract: Atom probe tomography was used to quantitatively assess grain boundary phase compositions and determine local segregation along the grain boundary before and after a 1000 h thermal exposure at 800 °C on an experimental powder processed Ni-base superalloy containing elevated levels of Nb. Due to high levels of refractory alloying elements at the grain boundary, a complex network of σ phase precipitates formed and the interfacial segregation profiles were studied. Although elemental B segregates to grain boundaries and secondary phase interfaces, insufficient levels are present to result in boride formation due to an enhanced solubility of B in the matrix phase. Graphical abstract: